KEGIATAN SOSIALISASI â€œGEMAR MAKAN IKANâ€ DAN PENGENALAN PRODUK PERIKANAN PADA ANAK USIA DINI, DESA PEMUTERAN, KECAMATAN GEROKGAK, BALI - Maknun, Luâ€™luâ€™il; Tsafitri, Anindita Moelya; Ananda, Riza Anastasia; Fazirra , Erra; Lestari, Dewi Putri; Sumsanto, Muhammad (Universitas Mataram, 2023)
Indonesia as a maritime country has an abundance of fish diversity. Although fish production is abundant, the level of fish consumption is declining. Fish is a source of high quality protein. Protein in fish has a complete composition and amount of essential amino acids. The fisheries and maritime sector supports the movement program to popularize eating fish (Gemarikan) designed by the Ministry of Maritime Affairs and Fisheries to become a national movement. This activity aims to increase knowledge and understanding as well as preventive action on the importance of the benefits of eating fish from an early age because of the many nutrients found in fish which are very useful for the growth and intelligence of children's brains and bone growth. This service activity is carried out using the counseling method and the introduction of fishery products. There are several stages in this activity starting from preparation, this stage is in the form of coordination regarding the place where the presentation of the material will be carried out, and operational preparation in the form of an application for permission to carry out socialization activities. Making rambutan shrimp products, presenting materials and distributing products.